Abundance measurements of Titan’s stratospheric HCN, HC3N, C3H4, and CH3CN from ALMA observations - Thelen, A; Nixon, C; Chanover, N; Cordiner, M; Molter, E; Teanby, N; Irwin, P; Serigano, J; Charnley, S (Elsevier, 2018)
Previous investigations have employed more than 100 close observations of Titan by the Cassini orbiter to elucidate connections between the production and distribution of Titan’s vast, organic-rich chemical inventory and its atmospheric dynamics. However, as Titan transitions into northern summer, the lack of incoming data from the Cassini orbiter presents a potential barrier to the continued study of seasonal changes in Titan’s atmosphere. In our previous work (Thelen et al., 2018), we demonstrated that the Atacama Large Millimeter/submillimeter Array (ALMA) is well suited for measurements of Titan’s atmosphere in the stratosphere and lower mesosphere ( km) through the use of spatially resolved (beam sizes  ≺ 1′′) flux calibration observations of Titan. Here, we derive vertical abundance profiles of four of Titan’s trace atmospheric species from the same 3 independent spatial regions across Titan’s disk during the same epoch (2012–2015): HCN, HC3N, C3H4, and CH3CN. We find that Titan’s minor constituents exhibit large latitudinal variations, with enhanced abundances at high latitudes compared to equatorial measurements; this includes CH3CN, which eluded previous detection by Cassini in the stratosphere, and thus spatially resolved abundance measurements were unattainable. Even over the short 3-year period, vertical profiles and integrated emission maps of these molecules allow us to observe temporal changes in Titan’s atmospheric circulation during northern spring. Our derived abundance profiles are comparable to contemporary measurements from Cassini infrared observations, and we find additional evidence for subsidence of enriched air onto Titan’s south pole during this time period. Continued observations of Titan with ALMA beyond the summer solstice will enable further study of how Titan’s atmospheric composition and dynamics respond to seasonal changes.